2017
DOI: 10.1308/rcsann.2017.0016
|View full text |Cite
|
Sign up to set email alerts
|

The utility of the radionuclide probe in parathyroidectomy for primary hyperparathyroidism

Abstract: INTRODUCTION Parathyroidectomy is the definitive treatment for primary hyperparathyroidism but the intraoperative identification of adenomas is challenging. The aim of this study was to evaluate the utility of a radionuclide probe (RNP) in addition to intraoperative parathyroid hormone ( IOPTH) measurement as an intraoperative diagnostic adjunct in patients undergoing parathyroidectomy for primary hyperparathyroidism. METHODS This was a retrospective cohort study of patients treated between 2004 and 2015 in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 18 publications
(14 reference statements)
0
3
0
Order By: Relevance
“…It can be caused by, for example, concomitant thyroid disease, such as an undiagnosed follicular thyroid adenoma. Nevertheless, these cases are rare and usually apparent on gross examination by the operating surgeon [ 18 ]. In the present study, only two such cases were observed.…”
Section: Discussionmentioning
confidence: 99%
“…It can be caused by, for example, concomitant thyroid disease, such as an undiagnosed follicular thyroid adenoma. Nevertheless, these cases are rare and usually apparent on gross examination by the operating surgeon [ 18 ]. In the present study, only two such cases were observed.…”
Section: Discussionmentioning
confidence: 99%
“…The principle of radionuclide-facilitated diagnosis of BC is illustrated in Figure 2. A common radionuclide cancer therapy is composed of three interconnected parts: A cancer cell-surface specific targeting molecule, a synthetic binding molecule that can specifically bind to the targeting molecule (called a linker), and a radionuclide-labeled chelator that is linked to the binding molecule (Figure 2) (57)(58)(59). All these three parts plus the specific surface marker on the cancer cells ensure the radionuclides target BC with high specificity and a high affinity, excluding potential off-target effects.…”
Section: Radionuclide Diagnosis In Breast Cancermentioning
confidence: 99%
“…A presumptive diagnosis of PHPT was made which met criteria for surgery due to the presence of osteoporosis (11). She underwent a minimally invasive, radio-guided parathyroidectomy of the left superior parathyroid gland (12). Pathology confirmed a 1.715-g left superior parathyroid adenoma measuring 2.5 × 1.7 × 0.8 cm.…”
Section: Case Reportmentioning
confidence: 99%